Porous iron and preparation method thereof

By using PMMA powder, carbon powder and solid wax as pore-forming agents, and using granulation and multi-step removal processes, the problems of low porosity and uneven porosity are solved, and porous iron preparation with high porosity and uniformity are achieved.

CN119566306AActive Publication Date: 2025-03-07FIRST SEMICON MATERIALS

Patent Information

Application Number
CN202411812616.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-07
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

In the prior art, when preparing porous iron, the residual porosity leads to low and uneven pores, and simple mixing leads to uneven pore distribution.

Method used

PMMA powder, carbon powder and solid wax are used as pore-forming agents, and the pore-forming agent is evenly distributed through granulation process, and the pore-forming agent is gradually removed through degreasing, combustion, reduction, sintering and other steps to improve the porosity and uniformity of porous iron.

Benefits of technology

The porosity and pore uniformity of porous iron are significantly improved, ensuring high quality and performance of the finished product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119566306A_ABST
    Figure CN119566306A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metal materials, and discloses a preparation method of porous iron, which specifically comprises the following steps: step 1, granulating iron powder, PMMA (polymethyl methacrylate) powder and carbon powder to obtain granulated powder; 2, mixing the granulation powder obtained in the step 1 with solid wax which is solid at normal temperature to obtain a mold pressing material; 3, the mold pressing material prepared in the step 2 is subjected to compression molding, and a green body is obtained; and 4, the green body obtained in the step 3 is degreased, burnt, reduced and sintered, and the finished porous iron is obtained. According to the porous iron, the raw materials are firstly granulated and then mixed with the PE wax, so that the pore effect of the finished product in both macroscopic and microscopic levels is greatly improved, and meanwhile, the invention further discloses the porous iron.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal materials, and in particular relates to porous iron and a preparation method thereof. Background Art

[0002] Porous metal material is a new type of functional material that is developing rapidly today. It has the characteristics of good permeability, large specific surface area, good energy absorption and shock absorption performance, low thermal conductivity and electrical conductivity, etc. It can be prepared into filters, silencers, catalyst carriers, electrodes, etc., and is widely used in machinery, medicine, metallurgy, environmental protection and other fields.

[0003] Among the existing technologies for preparing porous iron, the more common one is the traditional powder metallurgy method, which is to mix the raw materials with the pore-forming agent, remove the pore-forming agent by thermal decomposition, hot leaching, etc. after forming, and finally sinter to obtain porous iron; the use of traditional pore-forming agents often leads to the inability to completely remove the pore-forming agent, and the residual pore-forming agent causes problems such as low porosity and uneven pores in the finished product. Moreover, simply mixing the raw materials with the pore-forming agent will directly lead to the problem of uneven pore distribution.

[0004] Therefore, the technical problem that needs to be solved in this case is: how to prepare porous iron materials with better porosity effects through the granulation process and the synergistic effect between the pore-forming agent. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing porous iron, which adopts PMMA powder, carbon powder and solid wax as pore-forming agents to achieve pore formation inside granulated powder and pore formation between granulated powders, and can significantly improve the porosity of porous iron.

[0006] At the same time, the present invention also provides porous iron prepared based on the above method.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] A method for preparing porous iron comprises the following steps:

[0009] Step 1: granulating iron powder, PMMA powder and carbon powder to obtain granulated powder;

[0010] Step 2: mixing the granulated powder obtained in step 1 with a solid wax that is solid at room temperature to obtain a molding material;

[0011] Step 3: pressing the molding material obtained in step 2 to obtain a green body;

[0012] Step 4: Degreasing, burning, reducing and sintering the green body obtained in step 3 to obtain finished porous iron.

[0013] In the research of the present invention, it is found that by first granulating the raw material and then mixing it with solid wax, the following effects are achieved: on the one hand, granulation can make the pore-forming agent PMMA powder and carbon powder distributed very evenly, wherein PMMA powder can ensure that the product has a good porosity; and carbon powder is a low-temperature support and a high-temperature combustion pore-forming agent. After the PMMA powder is removed, the material maintains a complete structure and is finally burned and removed, further improving the pore effect of the product at the microscopic level; on the second hand, the use of solid wax can make each particle more evenly distributed, which is conducive to improving the uniformity of the product pores. In addition, the solid wax is eventually removed, so that there are pores between the particles at the macroscopic level. The porous iron product obtained by the present invention has a greatly improved pore effect both at the microscopic level and at the macroscopic level.

[0014] Preferably, the iron powder is spherical with a particle size of 5-45um; the PMMA powder is spherical with a particle size of 20-300um; the carbon powder is spherical with a particle size of 20-300um; and the solid wax that is solid at room temperature is spherical with a particle size of 5-250um.

[0015] In some embodiments of the present invention, the particle size (particle size, diameter) of the iron powder is 5um, 10um, 15um, 20um, 25um, 30um, 35um, 40um or 45um;

[0016] In some embodiments of the present invention, the particle size of PMMA powder is 20um, 30um, 40um, 50um, 60um, 70um, 80um, 90um, 100um, 120um, 140um, 160um, 180um, 200um, 220um, 240um, 260um, 280um or 300um.

[0017] In some embodiments of the present invention, the particle size of the carbon powder is 20um, 30um, 40um, 50um, 60um, 70um, 80um, 90um, 100um, 120um, 140um, 160um, 180um, 200um, 220um, 240um, 260um, 280um or 300um.

[0018] In some embodiments of the present invention, the particle size of the solid wax is 5um, 10um, 20um, 30um, 40um, 50um, 60um, 70um, 80um, 90um, 100um, 120um, 140um, 160um, 180um, 200um, 220um, 240um or 250um.

[0019] Preferably, the granulation operation is to add iron powder, PMMA powder and carbon powder into a PVA solution for granulation, and the PVA solution is an aqueous solution with a concentration of 3 to 14 wt%.

[0020] The volume ratio of the total volume of the iron powder, PMMA powder and carbon powder to the volume of the PVA solution is 1:2-3.

[0021] Preferably, the iron powder, PMMA powder, carbon powder and solid wax are contained in the following amounts by volume percentage:

[0022]

[0023] In the present invention, the porosity of porous iron is the volume ratio of iron powder in all raw materials. The method of the present invention can prepare porous iron with a porosity of 50% to 95%.

[0024] Preferably, the forming in step 3 is cold press forming with a pressure of 50 MPa to 300 MPa.

[0025] Preferably, the degreasing temperature in step 4 is 95° C. to 130° C. for 0.5 to 2 h, and 250° C. to 280° C. for 1 to 3 h, and the atmosphere is air.

[0026] Preferably, the combustion temperature in step 4 is 700° C. to 1050° C., the duration is 1 to 3 hours, and the atmosphere is air.

[0027] Preferably, the reduction temperature in step 4 is 850° C. to 1050° C., the duration is 1 to 3 hours, and the atmosphere is hydrogen or carbon monoxide atmosphere.

[0028] Preferably, the sintering temperature in step 4 is 1150° C. to 1400° C., the sintering time is 2 to 5 hours, and the atmosphere is an inert gas atmosphere.

[0029] Preferably, the solid wax is paraffin or PE wax.

[0030] Meanwhile, a porous iron is also disclosed, which is prepared by the porous iron preparation method as described above.

[0031] The beneficial effects of the present invention are

[0032] By first granulating the raw material and then mixing it with solid wax, the following effects are achieved: on the one hand, granulation can make the pore-forming agent PMMA powder and carbon powder distributed very evenly, wherein PMMA powder can ensure that the product has a good porosity; and carbon powder is a low-temperature support and a high-temperature combustion pore-forming agent. After the PMMA powder is removed, the material maintains a complete structure and is finally burned and removed, further improving the pore effect of the product at the microscopic level; secondly, the use of PE wax can make each particle distributed more evenly, which is conducive to improving the uniformity of the product pores. In addition, the solid wax is eventually removed, so that there are pores between the particles at the macroscopic level. The porous iron product obtained by the present invention has a greatly improved pore effect both at the microscopic level and at the macroscopic level. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the SEM image of the finished product of Example 1;

[0034] Figure 2 This is the SEM image of the finished product of Example 2;

[0035] Figure 3 This is the SEM image of the finished product of Example 3. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Example 1

[0038] Prepare the raw materials according to the porosity of 95%: 50% vol, PMMA powder with a particle size of 150um, 35% vol, carbon powder with a particle size of 100um, 10% vol, PE wax powder with a particle size of 50um, and 5% vol, iron powder with a particle size of 15um.

[0039] Among them, the molecular weight of PMMA powder is 500,000 to 1 million, and the manufacturer is Arkema Altuglas.

[0040] Granulation: PMMA powder, carbon powder and iron powder were granulated using 8wt% PVA solution as solvent, the volume ratio of solvent to powder was 1:2, and the final drying moisture was controlled at 1wt% to 3wt% to obtain granulated powder.

[0041] Mixing: Mix the granulated powder and PE wax powder with a V-type mixer for 3 hours to obtain a molding material.

[0042] Cold pressing: Load the molding material into the mold and use a hydraulic press to cold press for 5 minutes at a pressure of 70MPa to obtain a green body.

[0043] Degreasing and burning: Place the green body in a muffle furnace, heat up at a rate of 5°C / min in an air atmosphere, heat to 110°C and keep warm for 0.5h, heat to 260°C and keep warm for 2h, heat to 900°C in an air atmosphere and keep warm for 2h, cool to room temperature with the furnace, and obtain a degreased oxidized material.

[0044] Reduction and sintering: The degreased oxidized material is placed in an atmosphere furnace, hydrogen is continuously introduced, the temperature is raised to 950°C and kept for 2 hours, and then nitrogen is continuously introduced and the temperature is raised to 1200°C and kept for 3 hours, and the furnace is cooled to obtain the finished product.

[0045] See the SEM picture of the finished product Figure 1 .

[0046] Example 2

[0047] Prepare the raw materials according to the porosity of 80%: 40% vol, PMMA powder with a particle size of 300um, 35% vol, carbon powder with a particle size of 300um, 5% vol, PE wax powder with a particle size of 250um, and 20% vol, iron powder with a particle size of 45um.

[0048] Among them, the molecular weight of PMMA powder is 500,000 to 1 million, and the manufacturer is Arkema Altuglas.

[0049] Granulation: PMMA powder, carbon powder and iron powder were granulated using 14wt% PVA solution as solvent, the volume ratio of solvent to powder was 1:2.5, and the final drying moisture was controlled at 1wt% to 3wt% to obtain granulated powder.

[0050] Mixing: Mix the granulated powder and PE wax powder with a V-type mixer for 3 hours to obtain a molding material.

[0051] Cold pressing: Load the molding material into the mold and use a hydraulic press to cold press for 3 minutes at a pressure of 300MPa to obtain a green body.

[0052] Degreasing and burning: the green body is placed in a muffle furnace, heated at a rate of 5°C / min in an air atmosphere, heated to 130°C and kept for 0.5h, heated to 280°C and kept for 1h, heated to 1050°C in an air atmosphere and kept for 1h, cooled to room temperature with the furnace, and a degreased oxidized material is obtained.

[0053] Reduction and sintering: The degreased oxidized material is placed in an atmosphere furnace, carbon monoxide is continuously introduced, the temperature is raised to 1050°C and kept for 1 hour, then argon is continuously introduced and the temperature is raised to 1400°C and kept for 2 hours, and the furnace is cooled to obtain the finished product.

[0054] See the SEM picture of the finished product Figure 2 .

[0055] Example 3

[0056] Prepare the raw materials according to the porosity of 50%: 30% vol, PMMA powder with a particle size of 20um, 15% vol, carbon powder with a particle size of 20um, 5% vol, PE wax powder with a particle size of 5um, and 50% vol, iron powder with a particle size of 5um.

[0057] Among them, the molecular weight of PMMA powder is 500,000 to 1 million, and the manufacturer is Arkema Altuglas.

[0058] Granulation: PMMA powder, carbon powder and iron powder were granulated using 3wt% PVA solution as solvent, the volume ratio of solvent to powder was 1:3, and the final drying moisture was controlled at 1wt% to 3wt% to obtain granulated powder.

[0059] Mixing: Mix the granulated powder and PE wax powder with a V-type mixer for 3 hours to obtain a molding material.

[0060] Cold pressing: Load the molding material into the mold and use a hydraulic press to cold press for 8 minutes at a pressure of 50MPa to obtain a green body.

[0061] Degreasing and burning: the green body is placed in a muffle furnace, heated at a rate of 5°C / min in an air atmosphere, heated to 95°C and kept for 2 hours, heated to 250°C and kept for 3 hours, heated to 700°C in an air atmosphere and kept for 3 hours, cooled to room temperature with the furnace, and a degreased oxidized material is obtained.

[0062] Reduction and sintering: The degreased oxidized material is placed in an atmosphere furnace, carbon monoxide is continuously introduced, the temperature is raised to 850°C and kept for 3 hours, then argon is continuously introduced and the temperature is raised to 1150°C and kept for 5 hours, and the furnace is cooled to obtain the finished product.

[0063] See the SEM picture of the finished product Figure 3 .

[0064] Comparative Example 1

[0065] Prepare the raw materials according to the porosity of 50%: 30% vol, PMMA powder with a particle size of 20um, 20% vol, carbon powder with a particle size of 20um, and 50% vol, iron powder with a particle size of 5um.

[0066] Among them, the molecular weight of PMMA powder is 500,000 to 1 million, and the manufacturer is Arkema Altuglas.

[0067] Granulation: Using 8wt% PVA solution as solvent and the volume ratio of solvent to powder being 1:3, PMMA powder, carbon powder and iron powder are granulated, and the final drying moisture is controlled at 1wt% to 3wt% to obtain granulated powder.

[0068] Cold pressing: The granulated powder is loaded into a mold and cold pressed with a hydraulic press for 5 minutes at a pressure of 70 MPa to obtain a green body.

[0069] Degreasing and burning: place the green body in a muffle furnace, heat up at a rate of 5°C / min, keep warm at 110°C for 0.5h, keep warm at 260°C for 2h, keep warm at 900°C for 2h, cool to room temperature with the furnace, and obtain the degreased oxidized material.

[0070] Reduction and sintering: The degreased oxidized material is placed in an atmosphere furnace, hydrogen is continuously introduced, the temperature is raised to 950°C and kept for 2 hours, and then nitrogen is continuously introduced and the temperature is raised to 1200°C and kept for 3 hours, and the furnace is cooled to obtain the finished product.

[0071] Comparative Example 2

[0072] Prepare the raw materials according to the porosity of 50%: 35% vol, PMMA powder with a particle size of 20um, 15% vol, PE wax powder with a particle size of 5um, and 50% vol, iron powder with a particle size of 5um.

[0073] Among them, the molecular weight of PMMA powder is 500,000 to 1 million, and the manufacturer is Arkema Altuglas.

[0074] Granulation: Using 8wt% PVA solution as solvent and the volume ratio of solvent to powder being 1:3, PMMA powder and iron powder are granulated, and the final drying moisture is controlled at 1wt% to 3wt% to obtain granulated powder.

[0075] Mixing: Mix the granulated powder and PE wax powder with a V-type mixer for 3 hours to obtain a molding material.

[0076] Cold pressing: The granulated powder is loaded into a mold and cold pressed with a hydraulic press for 5 minutes at a pressure of 70 MPa to obtain a green body.

[0077] Degreasing and burning: Place the green body in a muffle furnace, heat up at a rate of 5°C / min in an air atmosphere, heat to 110°C and keep warm for 0.5h, heat to 260°C and keep warm for 2h, heat to 900°C in an air atmosphere and keep warm for 2h, cool to room temperature with the furnace, and obtain a degreased oxidized material.

[0078] Reduction and sintering: The degreased oxidized material is placed in an atmosphere furnace, hydrogen is continuously introduced, the temperature is raised to 950°C and kept for 2 hours, and then nitrogen is continuously introduced and the temperature is raised to 1200°C and kept for 3 hours, and the furnace is cooled to obtain the finished product.

[0079] Comparative Example 3

[0080] It is generally the same as Example 1, except that no PMMA powder is added to the raw materials.

[0081] Performance Testing

[0082] SEM test equipment model: German Zeiss sigma300 field emission scanning electron microscope

[0083] Carbon measurement equipment model: American LECO-844 carbon and sulfur analyzer

[0084] For specific test data, please refer to Table 1

[0085] Table 1 Performance test data of each sample

[0086]

[0087] Conclusion analysis:

[0088] The test data of Examples 1 to 3 are analyzed. According to the technical scheme of the present invention of first granulating the raw material and then mixing it with solid wax, when preparing porous iron with different porosities, the difference between the actual measured porosity of the obtained product and the porosity set when preparing the raw material is extremely small, and the smallest is 0.2% in Example 3; carbon powder serves as a skeleton support and a combustion pore-forming agent in the technical scheme of the present invention. The carbon content in the products of Examples 1 to 3 is very small, only about 10ppm, and the structure of the product is also very complete without collapse. It can be seen that by adopting the technical scheme of the present invention, there is almost no pore-forming agent residue in the prepared product, and the pore effect is unexpected.

[0089] Comparative Example 1 is based on Example 3, but the addition of PE wax powder is cancelled. It can be seen from the data that its porosity is only 45.7%. This is because in the degreasing stage, PE wax is the first pore-forming agent to be removed, which will make PMMA powder easier to remove during the removal process. Without PE wax powder, PMMA powder will remain and cannot be completely removed, resulting in an increase in carbon content in the finished product and a deterioration in porosity.

[0090] Comparative Example 2 is based on Example 3, but the addition of carbon powder is cancelled. As mentioned above, the carbon powder acts as a skeleton support and a combustion pore-forming agent, which can improve the strength of the product and further improve the porosity effect. Without the use of carbon powder, the strength of the material is insufficient, and the prepared porous iron product directly collapses.

[0091] Comparative Example 3 is based on Example 3, but the addition of PMMA powder is eliminated, resulting in experimental failure.

[0092] In summary, in the technical solution of the present invention, PMMA powder, PE wax powder and carbon powder are indispensable and must be used together to exert a synergistic effect. In addition to the granulation operation, the objective of the present invention can be achieved.

[0093] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing porous iron, characterized in that: The specific steps include: Step 1: granulating iron powder, PMMA powder and carbon powder to obtain granulated powder; Step 2: mixing the granulated powder obtained in step 1 with a solid wax that is solid at room temperature to obtain a molding material; Step 3: pressing the molding material obtained in step 2 to obtain a green body; Step 4: Degreasing, burning, reducing and sintering the green body obtained in step 3 to obtain porous iron.

2. The preparation method according to claim 1, characterized in that: The iron powder is spherical and has a particle size of 5-45um; the PMMA powder is spherical and has a particle size of 20-300um; the carbon powder is spherical and has a particle size of 20-300um; and the solid wax is spherical and has a particle size of 5-250um.

3. The preparation method according to claim 1, characterized in that: The contents of the iron powder, PMMA powder, carbon powder and solid wax are as follows:

4. The preparation method according to claim 1, characterized in that: The forming described in step 3 is cold pressing forming, and the pressure is 50MPa to 300MPa.

5. The preparation method according to claim 1, characterized in that: The degreasing temperature in step 4 is 95° C. to 130° C. for 0.5 to 2 h, and 250° C. to 280° C. for 1 to 3 h, and the atmosphere is air.

6. The preparation method according to claim 1, characterized in that: The combustion temperature in step 4 is 700° C. to 1050° C., the duration is 1 to 3 hours, and the atmosphere is air.

7. The preparation method according to claim 1, characterized in that: The reduction temperature in step 4 is 850° C. to 1050° C., the duration is 1 to 3 hours, and the atmosphere is hydrogen or carbon monoxide atmosphere.

8. The preparation method according to claim 1, characterized in that: The sintering temperature in step 4 is 1150° C. to 1400° C., the sintering time is 2 to 5 hours, and the atmosphere is an inert gas atmosphere.

9. The preparation method according to claim 1, characterized in that: The solid wax is paraffin or PE wax.

10. A porous iron, characterized in that: The porous iron is prepared by the method for preparing the porous iron as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Large-aperture high-porosity porous iron and preparation method thereof

    CN104451344A

  • Composition and porous ceramic atomization core containing continuous glass phase

    CN113149697A

  • High-strength low-shrinkage porous ceramic and preparation method thereof

    CN114988903A

  • Iron-based stainless steel porous material and preparation method thereof

    CN117900479A

  • Iron-based powder for powder metallurgy

    US20100224025A1

Cited By

  • A method for preparing porous iron with a porosity of 15-60%

    CN122503588A

  • A method for preparing porous iron by rapid solidification of iron-zinc alloy and continuous annealing and dezincification

    CN122644530A